View of U.S. spine surgeons regarding cost reduction measures - Pendi, Arif (J Spine Surg, 2018)
BACKGROUND: This is a cross-sectional study. Our objective is to survey spine surgeons’ views of responsibility to reduce healthcare costs, enthusiasm for cost reduction strategies, and agreement regarding roles in cost containment. The rising cost of healthcare has spurred debate about reducing expenditures. Previous studies have found that attitudes of anesthesiologists are predominantly in alignment with those of American physicians, but less is known about the views of spine surgeons. METHODS: After obtaining institutional approval, an electronic survey was disseminated to active members of AO Spine North America (AOSNA) via email. Respondents were asked eight questions about their age, gender, years in practice, practice facility, political views and opinions regarding management of healthcare costs. RESULTS: From 91 respondents, most were under the age of 60 years (87%), male (96%), and in practice for less than 30 years (91%), practiced at university hospitals (47%) and held politically conservative views (47%). Most responsibility was allocated to hospital and health systems, health insurance companies, pharmaceutical companies, and device manufacturers. Respondents were most enthusiastic about rooting out fraud and abuse and aware of their role in managing the cost of healthcare. Spine surgeons who were in practice for longer were more enthusiastic about reducing cost by reducing overall physician reimbursement via bundled payments, Medicare payment reduction, ending fee-for-service, penalizing surgeons for patient readmissions, and lowering compensation to individual spine surgeons. CONCLUSIONS: Spine surgeons allocated responsibility to reduce healthcare costs to healthcare systems, were most enthusiastic about eliminating wasteful spending, and were in agreement regarding their responsibility to control the costs of healthcare. Compared to US physicians of various specialties and anesthesiologists, spine surgeons assigned less responsibility to trials lawyers and expressed markedly less enthusiasm for limiting access to expensive treatments.